CATALYST DEVELOPMENT FOR THE CONVERSION OF CO2 TO AROMATIC COMPOUNDS - Alexander Christian S, Axel
Indonesia has a huge source of CO2 from natural gas in the Natuna Islands, where the CO2 content of natural gas reaches 72%. If an economically feasible CO2 capture technology is found, the next thing to think about is what to do with the CO2. This research focuses on the development of H-ZSM-5 zeolite catalyst for the conversion of ethylene into aromatic compounds which is a series of CO2 conversion into aromatic compounds. The series of research consisted of catalyst synthesis and catalyst activity test. The synthesized catalyst was then characterized using X-Ray Diffraction (XRD) to measure X-ray diffraction pattern, N2 Physisorption with Brunauer-Emmett-Teller (BET) method to calculate pore surface area and Barret-Joyner-Halenda (BJH) to calculate pore volume and pore diameter, NH3 Temperature Programmed Desorption (TPD) to measure acidity, and Scanning Electron Microscopy (SEM) to analyze the morphology and surface structure of zeolite. Then the activity test was carried out by reaction at a temperature of 320 ?, pressure of 1 bar, GHSV 1000 mL.gcat -1 .h-1 , and reaction time of 6 hours and analysis of gas and liquid samples using Gas Chromatography. Zeolite H-ZSM-5 basically has micropores that are not very optimal for the synthesis of aromatic compounds so this research focuses on the porosity mofidication of zeolite by adding CaCO3 and polyethylene glycol (PEG) as a template to encourage the formation of new larger pores. Based on the results obtained, the addition of CaCO3 and PEG as templates increases the pore surface area. The addition of PEG as a template effectively increases the existence of mesopores, while the addition of CaCO3 as a template actually reduces the existence of mesopores. The abundant existence of mesopores and large pore diameter increase the selectivity of aromatic compounds.